2017
DOI: 10.1017/s0950268817002229
|View full text |Cite
|
Sign up to set email alerts
|

Bovine leukaemia virus DNA in fresh milk and raw beef for human consumption

Abstract: SUMMARYBovine leukaemia virus (BLV) is the causative agent of enzootic bovine leucosis, which has been reported worldwide. BLV has been found recently in human tissue and it could have a significant impact on human health. A possible hypothesis regarding viral entry to humans is through the consumption of infected foodstuffs. This study was aimed at detecting the presence of BLV DNA in raw beef and fresh milk for human consumption. Nested PCR directed at the BLV gag gene (272 bp) was used as a diagnostic test.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 39 publications
0
32
0
5
Order By: Relevance
“…BLV is endemic in cattle in many countries where it causes leukosis in 2-5% of infected animals [109]. Its presence in meat and dairy products has been shown [110] and Buehring et al (2003) [111] found antibodies against BLV capsid antigen in 74% of human serum samples using immunoblotting. There are also several reports claiming an association of breast or colon cancer with BLV [73,112].…”
Section: Foodborne Animal Viruses With Unclear Zoonotic Potentialmentioning
confidence: 99%
“…BLV is endemic in cattle in many countries where it causes leukosis in 2-5% of infected animals [109]. Its presence in meat and dairy products has been shown [110] and Buehring et al (2003) [111] found antibodies against BLV capsid antigen in 74% of human serum samples using immunoblotting. There are also several reports claiming an association of breast or colon cancer with BLV [73,112].…”
Section: Foodborne Animal Viruses With Unclear Zoonotic Potentialmentioning
confidence: 99%
“…Previous studies report the presence of BLV in the bovine mammary epihtelium (Buehring et al, 1994;Yoshikawa et al, 1997). However, most recent works are focused in the detection of BLV infected mononuclear cells in milk (Jaworski et al, 2016;Kuckleburg et al, 2003), and its potential risk to human (Olaya-Galán et al, 2017;Sellers et al, 2008).…”
mentioning
confidence: 99%
“…In the other hand, variability of genotypes as well as results of structural and functional properties of its envelope proteins [36] provide useful information for research focused on vaccines production with specific strains, that in the case of Colombia, will be appropriate to include conserved epitopes shared between genotypes 1, 6 and 3 according to the results obtained in this study and previously reported [31]. In addition, phylogenetic studies are important to understand the geographical distribution of the virus and thus, identify conserved and hypervariable regions including specific mutations that could be related with different levels of virulence or pathogenicity [6,[37][38][39][40][41].…”
Section: Discussionmentioning
confidence: 82%
“…Given the importance of cattle industry in the country and in Latin America, it would be relevant if governmental entities and policy-maker agencies consider including the enzootic bovine leukosis as an official control disease, facilitating the diagnosis to the cattle industry members to identify infected animals, and furthermore, to control the dissemination of the virus focused in the future on the promotion of eradication programs, and likewise, minimizing the impact that BLV has on cattle and eventually on humans who consume bovine-derived food products [37].…”
Section: Discussionmentioning
confidence: 99%